1992
DOI: 10.1021/j100188a041
|View full text |Cite
|
Sign up to set email alerts
|

Activation of carbon dioxide on potassium-modified silver(111) single crystals

Abstract: of indole is a reversible reaction, and the number of related electrons is 2. Structure analysis of anodic precipitates suggests that the polymerization of indole is based on the formation of radical cations as intermediates.When the thermogravimetric analysis for the (PI)BF4 powder was conducted, the reaction rates for thermal decomposition were calculated by a computer connected to a thermal analyzer. A comparison between thermal characteristics of the (PI)BF4 and other polyindole-and polyaniline-based polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…RAIRS exhibits no detectable CO stretching mode between 2000 and 2300 cm -1 . These results are consistent with literature; CO does not adsorb at 77 K on Ag(111).
1 RAIRS (left panel) and TPD (right panel) following a standard dose (see text) of CO on Ag(111) and Cl-modified, <θ Cl = 0.12>, Ag(111) at 77 K. The expanded portion of the RAIRS spectra details the shoulder on the high energy side of the 2163 cm -1 peak. The TPD curve from clean Ag is superimposed (dashed curve) on the TPD from Cl-modified Ag(111).
…”
Section: Resultssupporting
confidence: 88%
“…RAIRS exhibits no detectable CO stretching mode between 2000 and 2300 cm -1 . These results are consistent with literature; CO does not adsorb at 77 K on Ag(111).
1 RAIRS (left panel) and TPD (right panel) following a standard dose (see text) of CO on Ag(111) and Cl-modified, <θ Cl = 0.12>, Ag(111) at 77 K. The expanded portion of the RAIRS spectra details the shoulder on the high energy side of the 2163 cm -1 peak. The TPD curve from clean Ag is superimposed (dashed curve) on the TPD from Cl-modified Ag(111).
…”
Section: Resultssupporting
confidence: 88%
“…The probability of the dissociative chemisorption of CO 2 on Rh(111) at room temperature and at low pressure was calculated to be of the order of 10 −11 −10 −15 . , However, potassium due to its electron-donation character can reduce the work function of the metals and induce the activation of CO 2 . This was first demonstrated on a K-dosed Pd(100) surface, , followed by extensive studies on Rh(111), Pt(111), , Pd(111), , Ru(0001), Ag(111), Co(1010), Mo 2 C/Mo(100), Cu(110), and Cu(115). , Further enhancement of the electron transfer to CO 2 can be achieved by the illumination of adsorbed CO 2 , as was first demonstrated on the Rh(111) surface . In the present paper, an account is given on the photolysis of the CO 2 + K/Au(111) system.…”
Section: Introductionsupporting
confidence: 51%
“…11,12 However, potassium due to its electron-donation character can reduce the work function of the metals and induce the activation of CO 2 . This was first demonstrated on a K-dosed Pd(100) surface, 13,14 followed by extensive studies on Rh(111), [15][16][17] Pt(111), 18,19 Pd(111), 20,21 Ru(0001), [22][23][24] Ag(111), 25 Co(1010), 26 Mo 2 C/Mo(100), 27 Cu(110), and Cu(115). 28,29 Further enhancement of the electron transfer to CO 2 can be achieved by the illumination of adsorbed CO 2 , as was first demonstrated on the Rh(111) surface.…”
Section: Introductionmentioning
confidence: 98%
“…On the basis of these results it has been concluded that condensed TDF reacts with Li to yield at about room temperature LiD as the main reaction product. A det~iled analysis of all other mass fragments strongly suggest a mixture of cyclopropane, formaldehyde and CO as the most likely thermally desc·rbed 14 products of the adsorbed, activated species generated at lower temperatures.…”
Section: Discussionmentioning
confidence: 99%